Analytical Calculation of the RMS Value and the Spectrum of the DC-Link Current of a Dual-Inverter - Schiedermeier, Maximilian; Schlamp, Franziska; Rettner, Cornelius; März, Martin (IEEE Transactions on Power Electronics, 2022)
This article is focused on the analytic definition of the dc-link current of a dual-inverter. Therefore, a two-level dual-inverter for driving two independent three-phase electrical motors is considered. Space-vector modulation is taken into account as the modulation method of the inverter. Based on that, an analytic description is derived for the frequency spectrum as well as for the rms value of the dc-link current of a dual-inverter. Contrary to the current definitions known from previous publications, the expressions presented below are defined in solved form. Therefore, the use of integral or differential equation expressions is not necessary. In this way, a basis is created for calculating the dc-link current without computationally intensive numerical integration processes or SPICE simulations. Furthermore, this article includes the metrological verification of the novel expressions. The results discussed in this publication provide the basis for stabilizing the HV-dc system and for minimizing the dc-link capacitor load. Thus, they enable the dc-link capacitor of a dual-inverter to be downsized. Based on the presented definition of the dc-link current in solved form, the possibility of real-time optimization is created. Furthermore, the results outlined in this article form the foundation to derive the control optimization for a multiphase inverter.
CRIS-Team WoS Importer:2021-10-08

Dual-inverter control synchronization strategy to minimize the DC-link capacitor current - Schiedermeier, Maximilian; Rettner, Cornelius; Steiner, Marcel; März, Martin (2020 IEEE Vehicle Power and Propulsion Conference, VPPC 2020 - Proceedings, 2020)
This paper proposes the possible switching synchronization strategies of an automotive dual-inverter against the background of minimizing the RMS DC-link capacitor current. The publication mainly focuses on the straight-ahead motion of a rear axle with one electric drive per wheel. In addition to it, a dual-inverter consisting of two subinverters with a common DC-link capacitor is taken into consideration. These sub-inverters each have three phases and are based on a 2-level voltage-source-topology. To control the electrical machines, the continuous Space-Vector-Modulation strategy is used. For this application, different control signal synchronization strategies of the two sub-inverters of the dualinverter are presented. Apart from the existing strategies, this paper proposes a new method, which inherits a compromise between low complexity and high effectiveness. In contrast to previous publications, the resulting capacitor currents are quantified and subsequentlyevaluated. This novel quantification, which is dependent on the dual-inverter's operating point, provides a base for targeted dimensioning of the capacitor. Moreover, this forms the foundation for further investigations of vehicle's cornering, as well as for the possible synchronization of stand-alone inverters. In the context of this publication, the presented results are verified by experimentally determined data of a motor-inverter system.
CRIS-Team Scopus Importer:2021-04-19
Keywords: DC-link capacitor; Dual-inverter; Interleaved inverters; Space vector modulation (SVM); Voltage source inverter (VSI)

Effect of voltage ringing in SiC power modules on conducted EMI of traction inverters - Apelsmeier, Andreas; Rettner, Cornelius; März, Martin (PCIM Europe Conference Proceedings, 2020)
This analysis deals with fast switching automotive SiC half bridge power modules. In this context the effect of oscillations in the switching waveforms on conducted electromagnetic emissions and on parasitic noise currents is analysed. Therefore an analytic simulation method is implemented, which considers the ringing of the MOSFET voltage in a common mode model of a buck converter. Applying the model, the major influencing parameters are identified. Furthermore, the simulated noise levels are compared to the relevant electromagnetic compatibility limits. So an acceptable maximum of the ringing effects of the switching transients is proposed. Finally, the model is verified by measurements.
CRIS-Team Scopus Importer:2020-08-28

Effect of Voltage Ringing in SiC Power Modules on Conducted EMI of Traction Inverters - Apelsmeier, Andreas; Rettner, Cornelius; März, Martin (PCIM Europe Conference Proceedings, 2020)
This analysis deals with fast switching automotive SiC half bridge power modules. In this context the effect of oscillations in the switching waveforms on conducted electromagnetic emissions and on parasitic noise currents is analysed. Therefore an analytic simulation method is implemented, which considers the ringing of the MOSFET voltage in a common mode model of a buck converter. Applying the model, the major influencing parameters are identified. Furthermore, the simulated noise levels are compared to the relevant electromagnetic compatibility limits. So an acceptable maximum of the ringing effects of the switching transients is proposed. Finally, the model is verified by measurements.
CRIS-Team Scopus Importer:2020-12-11

Fast DC-link capacitor design for Voltage Source Inverters based on weighted total harmonic distortion - Rettner, Cornelius; Schiedermeier, Maximilian; Apelsmeier, Andreas; März, Martin (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2020)
Computationally very expensive circuit simulations are required to design the dc-link capacitance for automotive traction voltage source inverters. Thereby, the dc-link voltage ripple is, in contrast to grid connected inverters, the predominant dc-link capacitor design parameter in automotive inverters. In order to achieve minimal capacitance size, the operating point of maximal voltage ripple of any applied modulation strategy has to be detected. This research proposes an optimized dc-link capacitance design approach based on the weighted total harmonic distortion of the dc-link current, which reduces the overall simulation time from several days to a few minutes.
CRIS-Team Scopus Importer:2020-07-31
Keywords: DC-link capacitor design; DPWM; SVPWM; voltage ripple; VSI; weighted total harmonic distortion (WTHD)

Interference of automotive HV-DC-systems by traction voltage-source-inverters (VSI) - Schiedermeier, Maximilian; Rettner, Cornelius; Heilmann, Marcel; Schneider, Felix; März, Martin (2019 ITEC, 2019)
This paper presents a method to analyze and quantify the interference of an automotive HV-DC-system due to excitation currents emitted by the voltage-source-inverters. This process is explained by reference to an exemplary HVsystem of a battery electric vehicle. As a part of this research, the HV-system’s modelling, a strategy for its parametrization as well as a metrological verification, based on impedance comparison is exposed. The HV-system’s impedance information is sufficient for validation. However, it does not allow to identify potentially dangerous excitation frequencies. Hence, an instrument in order to make possibly critical points of HV-system transparent is introduced. This instrument is the weak-point analysis which is based on current ratio transfer functions, generated by a state space model that describes the HV-system. As a result, component specific critical excitation frequencies are deduced and again metrologically validated. Furthermore, results from a previous publication are taken into account and combined with the critical frequencies, obtained later in this research. Finally, operating points of traction inverters, electric engines and therefore of the vehicle are determined which might be individually critical for each HVsystem’s components. Comprising, this paper offers a common thread on how to avoid damages to the HV-system’s components. This is achieved by influencing the dimensioning as well as by the definition of worst case operating points for an already existing System.<br
Keywords: Voltage source inverter (VSI); High voltage system (HV-system); Space vector pulse width modulation (SVPWM); DClink current harmonics; Impedance; Electric vehicles (EVs); Stability analysis; DC-link resonance

Model for Conducted Emission of SiC Power Modules for automotive traction Inverter-Comparison to behaviour-based Model - Apelsmeier, Andreas; Rettner, Cornelius; März, Martin (2020 IEEE 21st Workshop on Control and Modeling for Power Electronics, COMPEL 2020, 2020)
This paper presents a simulation approach to predict conducted electromagnetic emission of silicon carbide power modules applied in automotive inverters for electric drivetrains. The proposed time domain model is developed for standard circuit simulators and is directly adapted to the standardized measurement procedure of CISPR 25 from 150 kHz to 108 MHz. The main purpose of the paper andthe presented model is, to verify the quality, the accuracy and the level of confidence of a faster, behaviour-based approach, which uses idealized switching transients instead of detailed semiconductor models. Thus, the focus is on the detailed modeling of the power modules, the semiconductors and their switching behaviour, but not on the overall inverter characteristics. As a consequence theinverter is reduced to a buck converter. For the silicon carbide semiconductors, the provided accurate supplier MOSFET models are used. The electric environment of the converter is modeled by simplified equivalent circuits. Besides the differences due to the smoother waveforms of the accurate MOSFET models, the great impact of the voltage dependent drain source capacitance is identified and analysed. This results in a non-linear system behaviour. Finally, the model and the findings are verified by measurements.
CRIS-Team Scopus Importer:2021-04-19
Keywords: conducted emission; Electromagnetic compatibility (EMC); electromagnetic interference (EMI); mosfet model; silicon carbide (SiC); simulation model; traction inverter

SiC Power Module with integrated RC-Snubber Design for Voltage Overshoot and Power Loss Reduction - Rettner, Cornelius; Schiedermeier, Maximilian; Apelsmeier, Andreas; Heckel, Thomas; Diepgen, Antonia; Klische, Alexander; Dirksen, Daniel; März, Martin (2020 CIPS, 2020)
The maximum voltage overshoot of SiC MOSFETs in power modules limits the switching speed of voltage source inverters in electric vehicles. As the efficiency increases with faster switching transitions, decreased commutation loop inductances allow higher switching speeds at same voltage overshoot level and extend the vehicle’s range. In this research, a SiC power module including an integrated RC-snubber is designed to increase the switching speed at same voltage overshoot. The RC-snubber acts as a damped low inductance commutation loop filtering the switching transients and suppressing the ringing, whereas the low frequency components are filtered by the dc-link capacitor. To meet the target of increased system efficiency, the losses of all inverter components are analyzed for space-vector modulation (SVPWM).<br

Voltage ripple analysis based on DC-link current harmonics for Voltage Source Inverters - Rettner, Cornelius; Jacob, George; Schiedermeier, Maximilian; Apelsmeier, Andreas; März, Martin (2019 IEEE COMPEL, 2019)
The voltage ripple is the predominant dc-link capacitor design parameter in automotive traction voltage source inverters. Therefore, the reduction of the voltage ripple results in the decrease of the dc-link capacitance. In this research, the voltage ripple dependencies are analyzed for the space vector and the discontinuous space vector modulation, which lays a foundation in reducing the capacitance size based on new control methods. Hence, the dc-link current harmonics are analyzed for different sets of operating points and their effects on the voltage ripple are explained. Furthermore, the similarity of the dc-link rms current for these two modulation schemes is described.<br
Keywords: Dc-link voltage ripple; Dc-link current harmonics; Dc-link capacitor; Voltage source inverter VSI; State space model